Flexible, mechanically robust, multifunctional and sustainable cellulose/graphene nanocomposite films for wearable human-motion monitoring. (10th November 2022) - Han, Sensen; Wang, Pengcheng; Zhou, Yi; Meng, Qingshi; Aakyiir, Mathias; Ma, Jun
Abstract: The recent sensing technology development for flexible electronics has led to applications in intelligent robots, human-machine interfaces and health monitoring. However, it is challenging to combine ultra-light weight, high durability and flexibility, rapid response and simple fabrication within a single sensor. We herein report a cost-effective, sustainable preparation route for such a sensor, through (i) self-assembling cellulose nanofibers (CNFs) and graphene nanoplatelets modified by Triton X-100 (X-100-GNPs) and (ii) simply filtrating the mixture. X-100-GNPs were found to relatively uniformly disperse in the CNF matrix due to strong interfacial interactions. A nanocomposite film containing 23.76 vol% of GNPs displayed an electrical conductivity of 9.67 S/cm with mechanical robustness – Young's modulus of 6.18 GPa and tensile strength of 173 MPa. The efficient conductive GNP network provided the nanocomposite film sensors with integration of rapid response (61 ms under 1.5 KPa) and high flexibility, sensitivity and durability over 10, 000 loading and unloading cycles at 1 Hz with 0–0.5% tensile strain. Used as a wearable strain sensor, the film demonstrated remarkable sensing capabilities in physiological signals, voice recognition, repression changes, muscle contraction and joint bending. Graphical abstract: Image 1